Cost effective analysis of open and laparoscopic inguinal mesh hernioplasty - Jain, Akshay; Kumar, Ameet; Patel, Neelesh; Patrikar, Seema (International Journal of Research in Medical Sciences, 2024)
Background: Inguinal Hernia mesh repair surgery is one of the most commonly conducted surgical procedures. Between two approaches: open and laparoscopic, which is better for the patient in terms of cost and outcome in terms of quality of life and return to economic activity. To facilitate comparability across studies, cost effectiveness analysis requires measurement of both costs and quality adjusted life years (QALY). Methods: Descriptive, observational study which entails classifying costs, identifying cost centres, tracing all costs related to the elective procedures for inguinal mesh hernioplasty by both open and laparoscopic methods followed by checking the Quality of life pre and post-surgery of these patients through the EQ-5D-3L by telephonic interview. A Cost Effective analysis was conducted by the end of the study. Based on available data, we took 35 cases of laparoscopic procedure and 45 cases of open surgery as a universal sample size. Results: Traditional costing showed a difference of approximately INR 3245.93/- in the 2 procedures with laparoscopic surgery being costlier. Significant improvements were noted in patients post laparoscopic surgeries with less people complaining of post operative pain/discomfort and early resumption of daily activities and mobility within a month after the surgery. ICER is tilted in favour of laparoscopic surgeries by a value of Rs 1,08,197.66 per QALY. Conclusions: The difference in cost is minimal but the difference in the QALY scores and ultimately the ICER determines that laparoscopic surgery has an edge over open surgery in terms of outcome and patient comfort.